Budaya Populer dalam Politik di Indonesia - Imron Rosidi; Khotimah Khotimah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
Popular culture has actually a relationship with politics in Indonesia. In politics, media are used by a candidate to campaign and advertise. With the rise of television and social media, popular culture has manifested more in political arena. This is understandable because in recent political system being a popular politician is crucial because those who are popular are tended to be elected during elections. This paper attempts at analyzing the relationship of popular culture and Indonesian politics. This article finds that politics in popular culture has caused the reinforcement of identity politics in contemporary Indonesia. Secondly, it has supported the rise of hoaxes so that the fragmentation of grassroot society has been in a serious condition.